2015
DOI: 10.1088/1367-2630/17/2/023010
|View full text |Cite
|
Sign up to set email alerts
|

Ac impedance of A4C60fullerides under pressure

Abstract: Three A 4 C 60 compounds, with A = Li, Na and K, have been studied by impedance spectroscopy between 100 and 293 K at pressures up to 2 GPa. The results are in very good agreement with earlier dc resistance studies and with data from the literature. For all three materials the measured conductivity can be fitted by a sum of at least two Arrhenius terms. The band gaps derived from the resistance data, 0.3 eV for Na 4 C 60 and 0.5 eV for K 4 C 60 , are in excellent agreement with data measured by other methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In our view 12 , above the 125 K onset of Li + ionic diffusion to about ambient temperatures the DC conductivity arises mainly from the ionic conductivity, σ ion involving all Li ions. (Sundqvist et al 18 raised, however some doubts about this). On the other hand, we suggest that the microwave conductivity is the electronic conductivity σ el at 10 GHz associated with a small concentration of charged defects.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In our view 12 , above the 125 K onset of Li + ionic diffusion to about ambient temperatures the DC conductivity arises mainly from the ionic conductivity, σ ion involving all Li ions. (Sundqvist et al 18 raised, however some doubts about this). On the other hand, we suggest that the microwave conductivity is the electronic conductivity σ el at 10 GHz associated with a small concentration of charged defects.…”
Section: Resultsmentioning
confidence: 98%
“…14]. The electronic properties under pressure and calorimetric measurements of Li, Na and K doped fullerides were carried out in detail by the group of Sundqvist et al [15][16][17][18][19] . The ionic conductivity depends also on other factors than the barrier between sites; counter-intuitively, the DC conductivity of Li 4 C 60 polymer increases under pressure.…”
mentioning
confidence: 99%
“…In our view 12 , above the 125 K onset of Li + ionic diffusion to about ambient temperatures the DC conductivity arises mainly from the ionic conductivity, σ ion involving all Li ions. (Sundqvist et al 18 raised, however some doubts about this). On the other hand, we suggest that the microwave conductivity is the electronic conductivity σ el at 10 GHz associated with a small concentration of charged defects.…”
Section: B Electronic and Ionic Conductivities Inmentioning
confidence: 98%
“…In the solid-state, C 60 molecules form a face centered cubic (FCC) molecular crystal, and solid-state C 60 finds use as components in photovoltaics, supercapacitors, photomasks, and lubricants . When intercalated with alkali and alkali earth ions, solid state C 60 is known to exhibit composition-dependent superconductivity, tunable optical properties, room temperature high ZT thermoelectricity, and notably, superionic conductivity. However, the high ionic conductivity of lithium-doped crystalline C 60 is a point of contention and pertinent investigations have shown that electronic and mixed electronic–ionic contributions need to be considered as well. , Thus, despite past valuable experimental and simulation investigations, fundamental questions still remain on the extent of ionic conductivity and the underlying diffusive pathways that dictate ionic motion in C 60 solids . Unraveling such questions can shed further light on the utility of C 60 structures as potential components of alkali ion batteries, especially since there have been past efforts in integrating them both as electrode materials as well as interphase materials for ensuring the interfacial integrity of electrodes in lithium-ion batteries (LIB).…”
Section: Introductionmentioning
confidence: 99%